Association Between Igf- 1 Gene Polymorphisms And Body Weight In Nigeria Locally Adapted Turkeys (2018)
The insulin-like growth factor 1 (IGF-1) gene polymorphism plays important roles in development, growth and reproduction. Genetic intervention for the improvement o f Nigeria locally adapted turkeys based on growth rate and higher mature weight is important. This study was aimed at investigating the association between IGF-1 gene polymorphism and body weights in Nigeria locally adapted turkeys using PCR-RFLP method. Fifty poults were randomly selected for DNA analysis at 10 weeks. Zymo Miniprep kit was used for genomic DNA extraction from blood samples and 529bp fragment o f intron 2 o f IGF-1 gene was amplified. The genetic structure o f the population was analysed using POPGENE 32 software. Association o f the genotypes with body weight was evaluated using the General linear model of SAS 9.2. The enzyme digested products revealed A and B alleles with frequencies o f 0.61 and 0.39 respectively. Two genotypes A A (0.38) and AB (0.62) were detected. Chi-square test (0.001830) for Hardy-Weinberg equilibrium showed that the population sampled was not in equilibrium for the gene investigated. Also, significant association was not observed between IGF-1 polymorphs and body weight at 4, 8 and 12 weeks o f age in Nigeria locally adapted turkeys.